New Normal in the Post-COVID-19 of the Elders, Maeka Sub-District, Muang District, Phayao Province: no - จันทร์แดง, ประยงค์ (วารสารวิจัยและนวัตกรรมท้องถิ่น, 2023)
This research aims at 1) studying forms of the so called ‘new normal’ adopted by the elders in Maeka Sub-district, Muang District, Phayao Province, and 2) proposing how to adjust to the new normal after the COVID-19 epidemic for the elders. The data were collected by means of observations, non-formal interviews, and focus group discussions drawn from the 40 informants consisting of visiting lecturers, volunteer teachers, and elderly students in Elderly Learning Center of Wat Maekahuaykhian, Maeka Sub-district. It was found that the so called ‘new normal’ is a type of new way of life after the pandemic of COVID-19 throughout the country since 2020. It significantly affected the forms of elders’ living in Maeka Sub-district in 4 aspects: 1) beliefs and traditions with lesser congregations in the monastic affairs, festivals and traditions, 2) health care with more awareness in life such as wearing masks, keeping personal distances, 3) the economic difficulties with more bills concerning the medical payments such as masks, sanitizing alcohol, and 4) social relations with fewer usual gatherings and celebrations. For the lessons learnt of how to adjust in accordance with the situations, it was found that there should be the fourfold mode of living: ‘learning, accepting, adjusting, and changing’. That is to say, 1) being open-minded to ever learn new emerging things such as COVID-19, 2) being mindful and accepting it as a temporary threat, 3) adjusting behaviors in accordance with the pandemic, and 4) changing into the new normal. Keywords: New Normal, COVID-19, Adjustments, Elders